Adherence to implementing physical distancing and other COVID-19 preventive measures and its barriers among adults in Arba Minch town, Southwest Ethiopia: A lesson learned from the pandemic. - Teklu Wegayehu; Tsegaye Yohannes; Chuchu Churko; Alemayehu Bekele; Mekuria Asnakew Asfaw (PLoS ONE)
Background Globally, as of March 2024, the number of confirmed Coronavirus Disease 2019 (COVID-19) cases and deaths were over 774 million and seven million, respectively. Since there are no proven treatment in place against the disease, controlling strategy mainly rely on preventive measures. However, data on the extent of implementing physical distancing and other preventive measures during the pandemic of COVID-19 were inadequate in the study setting. This study is, therefore, documenting these gaps among people in Arba Minch town, South Ethiopia. Methods We conducted a community-based cross-sectional survey and qualitative study at Arba Minch in June 2020. Quantitative data were collected using an interviewer-administered questionnaire and check-list from study participants (head of household or any adult ≥18 years old in a household) and analyzed using SPSS version 20. Qualitative data were collected using key informant interviews (KIIs) and analyzed by using a thematic approach. Results Of the total surveyed adults (459), only 43.6% achieved above the mean score on adherence to implementing preventive measures of COVID-19. We found that 29.8% of participants kept physical distancing, only 37.7% of study participants had face-mask use practice, 20.5% had hand sanitizer use practice, 42.5% of participants avoided attendance in public gatherings, 44.7% stopped touching their nose, eye, and mouth, 55.6% practiced stay at home, and 60% had frequent hand washing practice. Besides, the main emerged barriers of adherence to implementing COVID-19 preventive measures were poverty, distrust of government, misbelief, lack of ownership, lack of attention and sustained actions, lack of ownership, socio-cultural influence, lack of coordination and leadership. Conclusions The finding of this study suggests inadequate adherence to implementing COVID-19 preventive measures in adults in Arba Minch. Although inadequately implemented, a lot of lessons have been learned from COVID-19 pandemic preventive measures that would help in prevention and control of such a pantomimic disease happened.